2015
DOI: 10.1111/tri.12719
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of kidney paired donation transplants in relation to shipping and cold ischaemia time

Abstract: SUMMARYTo assess the impact of shipping distance and cold ischaemia time (CIT) of shipped organs in a kidney paired donation (KPD) programme, we evaluated the outcomes of the initial 100 kidney transplants performed in the Australian KPD programme. In a 44-month period, 12 centres were involved in fifteen 2-way, twenty 3-way, one 4-way and one 6-way exchanges. Sixteen kidneys were transplanted at the same hospital (CIT 2.6 AE 0.6 h) and 84 required transport to the recipient hospital (CIT 6.8 AE 2.8 h). A spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…In our study, a prolonged CIT behaved as an independent risk factor for DGF, in which for each hour of CIT, the risk of DGF was increased by 10% (OR 1.10, 95% CI 1.04–1.16); however, a prolonged CIT was not a risk factor for renal graft dysfunction or AR 1 year after renal transplantation – a finding similar to that reported by previous studies. [ 3 5 15 ] Opelz et al . reported that the increase in CIT up to 18 hours did not increase the risk of renal graft loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, a prolonged CIT behaved as an independent risk factor for DGF, in which for each hour of CIT, the risk of DGF was increased by 10% (OR 1.10, 95% CI 1.04–1.16); however, a prolonged CIT was not a risk factor for renal graft dysfunction or AR 1 year after renal transplantation – a finding similar to that reported by previous studies. [ 3 5 15 ] Opelz et al . reported that the increase in CIT up to 18 hours did not increase the risk of renal graft loss.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] Delayed graft function (DGF) is among the known risk factors for renal graft loss,[ 1 2 ] a complication that occurs in up to 50% of patients of deceased donors. [ 3 4 5 6 ] Different risk factors have been associated with the risk of DGF, among them are the creatinine values of the donor and the cold ischemia time (CIT),[ 1 3 ] the latter defined as the period elapsed after the cessation of circulation, when perfusion begins with preservation solutions, until the beginning of the vascular anastomosis in the renal graft recipient. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, transport of living donor kidney may be a feasible alternative to donor travel in multicenter simultaneous KPD program where CIT < 8 h[8,9]. Australian program preferred to ship donor kidneys rather than the donor despite prolonged CIT for interstate exchanges[10]. In India, there is only one report of multicenter simultaneous KPD of 5 DRP[11].…”
Section: Discussionmentioning
confidence: 99%
“…The long term graft survival is not significantly affected when cold ischemia time is short (< 8 h). Despite prolonged cold ischemia time for interstate exchanges, the Australian kidney exchange program preferred to transport donor kidneys rather than kidney donors[60]. However, there is no multi-centre kidney paired donation transplant practice in India.…”
Section: Distribution Of Blood Group Types In Incompatible Donors Andmentioning
confidence: 99%